DIGITAL PEDAGOGY AND ITS ADVANTAGES (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
In the 21st century, the transition of the educational process to a digital environment has ushered in a new stage of human civilization - the era of digital transformation. As a result of this process, the term "digital pedagogy" was formed. This means not only using technological tools but also reorganizing the educational process based on new methodological approaches.